Legal Research in India: Challenges, Opportunities, and Emerging Trends - Veerabhadraiah C, (AG Volumes, 2025)
This review is a critical analysis of legal research in India based on its concept, scope, challenges, opportunities and current trends. It marks the shift of the classical doctrinal methods to the more interdisciplinary, technology-focused and empirical methods. The research paper presents structural issues like inadequate research infrastructure, insufficient empirical focus, language, and teaching-research imbalance, and also provides opportunities that are presented by judicial reform, digitalization, globalization, and broadening legal areas. It focuses on ethical principles, methodology, and the increasing applicability of socio-legal and policy-oriented research in enhancing the law-making, judicial procedures, and access to justice in India.